The Influence of Autonomy-Supportive Teaching on EFL Students’ Classroom Autonomy: An Experimental Intervention - Alrabai, Fakieh (Frontiers in Psychology, 2021)
Based on the framework of self-determination theory (SDT), this 2-wave longitudinal empirical investigation examined the actual practicality of certain strategies that have been theoretically acknowledged as having potential positive effect on English as a foreign language (EFL) learner’s autonomy. Strategies targeting learners’ self-determined learning in the classroom in terms of satisfying learner basic psychological needs (BPNs) of autonomy, competence, and relatedness as well as SDT key concepts such as learner sense of choice, intrinsic motivation, control over learning, goals and needs, and metacognitive skills were implemented in a treatment group for 12 weeks. A classroom observation was used to evaluate teachers’ autonomy-supportive teaching and a student self-report measure, and an observation were used to assess learners’ autonomy. The findings derived out from analyses of variance, covariance and a hierarchical regression revealed that the experimental intervention led to statistically significant increased EFL autonomy for learners in the experimental group. Learner perceived choice, autonomy support, competence, and intrinsic motivation mediated the relationship between teacher autonomy-supportive teaching and learner autonomy; with perceived choice being the strongest predictor of learner autonomy. These findings acknowledge the vital role of teacher autonomy-supportive teaching in promoting EFL learner autonomy and recommend that, beside satisfying their BPNs, students should always be granted a larger space of freedom of choice, more control over learning, and more involvement in decision-making process.